2010
DOI: 10.1016/j.neubiorev.2009.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral evidence for changes in dopamine system activity during adolescence

Abstract: Human adolescence has been characterized by increases in risk-taking, emotional lability, and deficient patterns of behavioral regulation. These behaviors have often been attributed to changes in brain structure that occur during this developmental period, notably alterations in gray and white matter that impact synaptic architecture in frontal, limbic, and striatal regions. In this review, we provide a rationale for considering that these behaviors may be due to changes in dopamine system activity, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
185
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(192 citation statements)
references
References 250 publications
(342 reference statements)
3
185
0
4
Order By: Relevance
“…Frank [44] and Frank and Claus [45] have suggested that phasic increases in DA that occur in response to positive feedback are related to D 1 receptor activity while decreases in DA after negative feedback are related to D 2 activity. If this is so, then the gender- and age-related differences that we have reported in the FRN can be mapped onto the sexual dimorphism seen in DA activity, DA receptor density and DA system maturation [22,23,46]. DA system changes during adolescence are more dramatic for males than females [22,23], and adult males have more D 1 receptors in the ventral striatum than females [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frank [44] and Frank and Claus [45] have suggested that phasic increases in DA that occur in response to positive feedback are related to D 1 receptor activity while decreases in DA after negative feedback are related to D 2 activity. If this is so, then the gender- and age-related differences that we have reported in the FRN can be mapped onto the sexual dimorphism seen in DA activity, DA receptor density and DA system maturation [22,23,46]. DA system changes during adolescence are more dramatic for males than females [22,23], and adult males have more D 1 receptors in the ventral striatum than females [47].…”
Section: Discussionmentioning
confidence: 99%
“…These reports are consistent with our finding that the FRN in males but not females is sensitive to the size of the win. Furthermore, D 2 receptor maturation begins and ends later than D 1 receptors and, if changes are more profound for males than females [46], this may explain why the FRN to losses seems markedly immature in boys compared to girls. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, these values were included in a partial correlation with SR scores, removing the effect of age. We included age as a covariate because previous evidence has shown that this variable is related to brain activity within the dopaminergic system [40,41]. The correlation analysis threshold was set to p,.05 Bonferroni FWE corrected.…”
Section: Personality Analysismentioning
confidence: 99%
“…Of particular relevance for the current study, intermediate phenotypes, such as brain mechanisms at neurochemical, structural, and functional levels (Meyer-Lindenberg and Weinberger, 2006), change substantially during maturation and senescence. Thus, it has been hypothesized that age-related differences in brain resources might modulate genotype-phenotype relations during different life periods Posner et al, 2006;Wahlstrom et al, 2010). Genes related to the neurotransmitter dopamine (DA) represent a case in point.…”
Section: Introductionmentioning
confidence: 99%